Method for producing sulfide solid electrolytes

JP2026166681APending Publication Date: 2026-10-14IDEMITSU KOSAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025059780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、効率的に良好な粒度分布を有する硫化物固体電解質を得ることができる硫化物固体電解質の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166681000001
    Figure 2026166681000001
  • Figure 2026166681000002
    Figure 2026166681000002
Patent Text Reader

Abstract

The objective is to provide a method for producing a sulfide solid electrolyte that efficiently yields a sulfide solid electrolyte with a good particle size distribution. [Solution] By calcining the raw material contents, The sulfide solid electrolyte obtained by the aforementioned calcination and the solvent are wet-ground using a pulverizer to obtain a sulfide solid electrolyte slurry, and A method for producing a sulfide solid electrolyte, comprising drying the sulfide solid electrolyte slurry using an air-jet dryer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for producing a sulfide solid electrolyte. [Background technology]

[0002] In recent years, with the rapid proliferation of information-related devices and communication equipment such as personal computers, video cameras, and mobile phones, the development of batteries used as their power sources has become increasingly important. Among batteries, lithium-ion batteries are attracting attention due to their high energy density. Currently available lithium-ion batteries use electrolytes containing flammable organic solvents, necessitating the installation of safety devices to suppress temperature rise during short circuits, as well as improvements in structure and materials to prevent short circuits. In particular, for automotive applications, there is a demand for higher capacity and higher output, making safety considerations for conventional electrolyte-based batteries increasingly important. In contrast, lithium-ion batteries that use a solid electrolyte, making the battery entirely solid, do not use flammable organic solvents within the battery, thus simplifying safety devices and offering advantages in manufacturing cost and productivity.

[0003] Sulfide solid electrolytes are known as solid electrolytes used in lithium-ion batteries. From the standpoint of performance and manufacturing in all-solid-state lithium batteries, sulfide solid electrolytes with small particle sizes are required. In all-solid-state lithium batteries, the positive electrode material, negative electrode material, and electrolyte are all solid, so if the particle size of the sulfide solid electrolyte is small, it is easier to form contact interfaces between sulfide solid electrolytes themselves, and between the active material and the sulfide solid electrolyte, which has the advantage of improving the paths for ion conduction and electron conduction.

[0004] Patent Document 1 describes a method for producing a sulfide solid electrolyte, in which raw materials are crushed and mixed in a ball mill, then the resulting calcined product is coarsely ground, and then finely ground to achieve a predetermined particle size distribution. Patent Document 2 describes a method for producing a modified sulfide solid electrolyte powder, in which powdered sulfide solid electrolyte is flowed with a specific airflow using a dry classifier. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2020-126760 [Patent Document 2] International Publication No. 2023 / 276860 brochure [Overview of the project] [Problems that the invention aims to solve]

[0006] This invention has been made in view of the above circumstances, and aims to provide a method for producing a sulfide solid electrolyte that can efficiently obtain a sulfide solid electrolyte having a good particle size distribution. [Means for solving the problem]

[0007] The method for producing a sulfide solid electrolyte according to the present invention is: The process of calcining the raw materials. The sulfide solid electrolyte obtained by the aforementioned calcination and the solvent are wet-ground using a pulverizer to obtain a sulfide solid electrolyte slurry, and The method for producing a sulfide solid electrolyte includes drying the sulfide solid electrolyte slurry using an air-jet dryer. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide a method for producing a sulfide solid electrolyte that efficiently has a good particle size distribution. [Brief explanation of the drawing]

[0009] [Figure 1] This is a flowchart illustrating an example of a preferred embodiment of the manufacturing method of this embodiment. [Figure 2] This shows the volume-based particle size distribution of the sulfide solid electrolytes obtained in Example 1 and Comparative Example 1. [Description of Embodiments]

[0010] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") will be described. In the present specification, the upper limit and lower limit values related to the numerical ranges of "or more", "or less", and "to" are values that can be arbitrarily combined, and the numerical values of the examples can also be used as the upper limit and lower limit values.

[0011] (Findings Obtained by the Present Inventors to Arrive at the Present Invention) As a result of intensive studies aimed at solving the above problems, the present inventors have found the following matters and have completed the present invention. It is desired to control the particle size of the sulfide solid electrolyte according to its application. In addition, since both the electrode material and the separator material are applied by converting the powder of the sulfide solid electrolyte into an ink during the battery manufacturing process, if the sulfide solid electrolyte contains coarse particles, uniform application will be hindered. Therefore, the sulfide solid electrolyte is required to contain no coarse particles.

[0012] Generally, pulverization is performed to adjust the particle size of powder. The present inventors have found that depending on the pulverization conditions of the sulfide solid electrolyte and the drying conditions during drying for removing the solvent that may be contained in the sulfide solid electrolyte, the sulfide solid electrolyte tends to aggregate, which may increase the proportion of coarse particles contained in the sulfide solid electrolyte.

[0013] Accordingly, the present inventors focused on the properties of the sulfide solid electrolyte and studied the conditions for pulverization and drying of the sulfide solid electrolyte. In the production method described in Patent Document 1, the fired product (sulfide solid electrolyte) is pulverized, but there is no description related to flash drying after pulverization, and the above problem is not raised. Further, in the production method described in Patent Document 2, a dry classifier is used to flow powdery sulfide solid electrolyte together with a specific gas stream to modify the sulfide solid electrolyte, but there is no description related to flash drying a slurry containing the sulfide solid electrolyte, and the above problem is not raised.

[0014] Based on the above studies, the present inventors have found that by wet-pulverizing the sulfide solid electrolyte obtained by firing the raw material-containing material, and subjecting the resulting sulfide solid electrolyte slurry to flash drying, aggregation of the sulfide solid electrolyte is reduced, and a sulfide solid electrolyte having a favorable particle size distribution can be efficiently obtained. The sulfide solid electrolyte having a favorable particle size distribution contains no coarse particles, and exhibits excellent coatability when the sulfide solid electrolyte is applied as a solution or slurry.

[0015] (Regarding various aspects of the present embodiment) The method for producing a sulfide solid electrolyte according to the first aspect of the present embodiment is: firing the raw material-containing material, wet-pulverizing the sulfide solid electrolyte obtained by the firing and a solvent with a pulverizer to obtain a sulfide solid electrolyte slurry, and drying the sulfide solid electrolyte slurry using a flash dryer. This is a method for producing a sulfide solid electrolyte including the above steps.

[0016] In the present specification, the "sulfide solid electrolyte" means an electrolyte that contains sulfur atoms and remains solid at 25°C under a nitrogen atmosphere. In the present embodiment, the sulfide solid electrolyte is preferably a sulfide solid electrolyte containing lithium atoms, sulfur atoms and phosphorus atoms, and having ionic conductivity derived from lithium atoms.

[0017] The "sulfide solid electrolyte" includes crystalline sulfide solid electrolytes. In this specification, a crystalline sulfide solid electrolyte is a sulfide solid electrolyte in which a peak originating from the solid electrolyte is observed in the X-ray diffraction pattern in X-ray diffraction measurements, regardless of whether or not a peak originating from the raw material of the sulfide solid electrolyte is observed. That is, a crystalline sulfide solid electrolyte includes a crystal structure derived from the solid electrolyte, and may be a part of the crystal structure derived from the solid electrolyte, or may be entirely derived from the solid electrolyte.

[0018] The method for producing a sulfide solid electrolyte in this embodiment involves wet grinding the sulfide solid electrolyte obtained by calcining the raw material components, and then air-drying the resulting sulfide solid electrolyte slurry. This reduces aggregation of the sulfide solid electrolyte, allowing for the efficient production of a sulfide solid electrolyte with a good particle size distribution. Therefore, according to the method for producing a sulfide solid electrolyte in this embodiment, it is possible to obtain a sulfide solid electrolyte that does not contain coarse particles and has excellent coating properties when applied as a solution or slurry.

[0019] In this specification, "coating properties" refers to the ease of coating and the quality of the coated surface when a solution or slurry is applied. A sulfide solid electrolyte is said to have "excellent coating properties" to mean that when a solution or slurry containing the sulfide solid electrolyte is used for coating, it exhibits excellent workability and a good coated surface condition. Coating properties can be evaluated, for example, by the method described in the examples.

[0020] The method for producing a sulfide solid electrolyte according to the second embodiment of this embodiment is, in the first embodiment described above, The aforementioned airflow dryer is a spray dryer. That is the case.

[0021] In this embodiment, if the airflow dryer used for the production of the sulfide solid electrolyte is a spray dryer, aggregation of the sulfide solid electrolyte is further reduced, and a sulfide solid electrolyte with a better particle size distribution can be efficiently obtained. This sulfide solid electrolyte does not contain coarse particles and has superior coating properties when applied as a solution or slurry.

[0022] A method for producing a sulfide solid electrolyte according to the third embodiment of this embodiment is, in the second embodiment described above, The spray pressure in the aforementioned spray dryer is 0.01 to 0.8 MPa. That is the case.

[0023] When the spray pressure in the spray dryer is within the above range, the solvent in the sulfide solid electrolyte slurry can be sufficiently removed. Furthermore, aggregation of the sulfide solid electrolyte is further reduced, and a sulfide solid electrolyte with a better particle size distribution can be efficiently obtained.

[0024] The method for producing a sulfide solid electrolyte according to the fourth embodiment of this embodiment is, in the second or third embodiment described above, The droplet diameter of the spray liquid in the aforementioned spray dryer is 50 μm or less. That is the case.

[0025] When the droplet size of the spray liquid in the spray dryer is less than or equal to the above value, aggregation of the sulfide solid electrolyte is further reduced, and a sulfide solid electrolyte with a better particle size distribution can be efficiently obtained.

[0026] The method for producing a sulfide solid electrolyte according to the fifth embodiment of this embodiment is, in any one of the first to fourth embodiments described above, The sulfide solid electrolyte obtained by the aforementioned drying has a volume-based particle size distribution with a peak in the range of particle size between 0.1 μm and less than 10.0 μm. That is the case.

[0027] In the method for producing a sulfide solid electrolyte of this embodiment, the obtained sulfide solid electrolyte preferably has a peak in the particle size range of 0.1 μm or more and less than 10.0 μm in its volume-based particle size distribution. The sulfide solid electrolyte does not contain coarse particles and exhibits excellent coating properties when applied as a solution or slurry. The shape of the peak described above may be unimodal or multimodal (two or more peaks).

[0028] The method for producing a sulfide solid electrolyte according to the sixth embodiment of this embodiment is, in any one of the first to fifth embodiments described above, The sulfide solid electrolyte obtained by the aforementioned drying is used as an electrode. That is the case.

[0029] According to the method for producing a sulfide solid electrolyte of this embodiment, a sulfide solid electrolyte having a good particle size distribution can be obtained. This sulfide solid electrolyte does not contain coarse particles and can be suitably used as an electrode.

[0030] The method for producing a sulfide solid electrolyte according to the seventh embodiment of this embodiment is, in any one of the first to sixth embodiments described above, The aforementioned raw material contains lithium atoms, sulfur atoms, and phosphorus atoms. That is the case.

[0031] In the method for producing a sulfide solid electrolyte of this embodiment, it is preferable that the raw material contains the above-mentioned atoms.

[0032] The method for producing the sulfide solid electrolyte according to this embodiment will be described in more detail below, following the above-described aspects.

[0033] [Method for producing sulfide solid electrolytes] The method for producing a sulfide solid electrolyte of this embodiment (hereinafter also simply referred to as "the method of production of this embodiment") involves calcining the raw material in a calcination furnace, as shown in Figure 1. The sulfide solid electrolyte obtained by the aforementioned calcination and the solvent are wet-ground using a pulverizer to obtain a sulfide solid electrolyte slurry, and The method for producing a sulfide solid electrolyte includes drying the sulfide solid electrolyte slurry using an air-jet dryer.

[0034] (Casturing the raw materials) The manufacturing method of this embodiment includes calcining the raw material-containing material. This makes it possible to produce a sulfide solid electrolyte, preferably a crystalline sulfide solid electrolyte.

[0035] The above-mentioned raw material content may include solid electrolyte raw materials selected according to the sulfide solid electrolyte to be obtained, and preferably contains lithium atoms, sulfur atoms, and phosphorus atoms. Furthermore, since sulfide solid electrolytes preferably contain halogen atoms from the viewpoint of improving ionic conductivity, it is preferable that the raw material content further contains halogen atoms. More specifically, the raw material content is a content containing substances containing these atoms (hereinafter also referred to as "solid electrolyte raw materials"), and it is preferable that it contains two or more types of solid electrolyte raw materials.

[0036] As solid electrolyte raw materials included in the raw material composition, typically preferred materials include those containing at least two atoms selected from the above atoms, such as lithium sulfide; phosphorus trisulfide (P2S3), phosphorus pentasulfide (P2S5), etc., and those consisting of one atom selected from the above atoms, such as elemental phosphorus or elemental sulfur. Among these, lithium sulfide and phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5) are preferred, and among phosphorus sulfides, phosphorus pentasulfide (P2S5) is preferred.

[0037] The raw material may also contain halogen atoms, and examples of raw materials include substances containing halogen atoms. For example, lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; and elemental halogens such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2) are typically preferred.

[0038] The above-mentioned solid electrolyte raw materials can be used by blending them in a ratio that matches the composition of a sulfide solid electrolyte having a desired crystal structure. Examples of the blending ratio of lithium sulfide contained in the raw material to other solid electrolyte raw materials include those described in International Publication No. 2020 / 105737 (see paragraphs

[0024] to

[0028] ), etc. Furthermore, the solid electrolyte raw materials can also be appropriately selected from the substances exemplified in International Publication No. 2020 / 105737 (see paragraphs

[0020] to

[0022] ), etc.

[0039] It is preferable to pre-grind the raw materials to adjust their particle size. When pre-grinding, it is preferable to make the average particle size 20 μm or less, more preferably 15 μm or less, and even more preferably 12 μm or less. A grinder can be used to grind the raw materials, and container-driven grinders such as ball mills and bead mills are preferred, as are pin mills, which have a short processing time and allow for continuous grinding operations.

[0040] It is preferable to pre-mix the raw materials. There are no particular restrictions on the type of mixer that can be used for pre-mixing, but examples of preferred mixers include mechanical agitators, conical screw type mixers such as Nauta mixers, and high-speed agitators such as FM mixers.

[0041] Furthermore, it is preferable to mix and grind the raw material in a solvent. As the solvent used during mixing and grinding, nonpolar solvents such as hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents, and polar solvents such as solvents containing heteroatoms are preferably used, and it is preferable to use a combination of a nonpolar solvent and a polar solvent. When a combination of a nonpolar solvent and a polar solvent is used, aromatic hydrocarbon solvents, particularly toluene and ethylbenzene, are preferred as the nonpolar solvent, and nitrile solvents that have the property of azeotropic formation with aromatic hydrocarbon solvents such as toluene and are easily removed together with aromatic hydrocarbon solvents such as toluene are preferred as the polar solvent.

[0042] As equipment used for mixing and grinding the raw material components, preferred grinders include the grinders exemplified above as grinders that can be used for grinding the raw materials, planetary ball mills, vibratory mills, rolling mills, bead mills, and the like.

[0043] When the raw materials are mixed and ground using a solvent, the process may include drying the resulting fluid (usually a slurry) after mixing and grinding. The drying method can be any method that can remove the solvent, and can be performed using solid-liquid separation, drying by heating, reduced-pressure drying (vacuum drying), or a combination of these methods.

[0044] The heating temperature during calcination of the raw material-containing material can be appropriately selected according to the composition of the sulfide solid electrolyte to be obtained, for example, preferably 300°C or higher, more preferably over 300°C, even more preferably 320°C or higher, even more preferably 350°C or higher, and particularly preferably 380°C or higher. The upper limit is preferably 470°C or lower, more preferably 460°C or lower, even more preferably 450°C or lower, even more preferably 440°C or lower, and particularly preferably 430°C or lower. The heating time is preferably 1 minute to 6 hours, more preferably 1 minute to 2 hours, and even more preferably 5 minutes to 1 hour.

[0045] The firing process is preferably carried out in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or a reduced-pressure atmosphere (especially in a vacuum). Furthermore, firing can be carried out using firing furnaces such as stationary hearth kilns or rotary kilns.

[0046] (Sulfide solid electrolyte) The sulfide solid electrolyte obtained by the above calcination process has an argyrodite-type crystal structure. The argyrodite crystal structure is a crystal structure that basically has the structural framework of Li7PS6, with some of the P being replaced by Si. For example, Li 7-x P 1-y Siy S6, Li 7+x P 1-y Si y S6 (x is -0.6 to 0.6, y is 0.1 to 0.6). The argyrodite-type crystal structure represented by these compositional formulas is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks mainly appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°. Note that these peak positions may vary within a range of ±0.5°.

[0047] Examples of the compositional formula of the argyrodite-type crystal structure include Li 7-x-2y PS 6-x-y Cl x (0.8≦x≦1.7, 0<y≦-0.25x+0.5). The argyrodite-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks mainly appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Further, examples of the compositional formula of the argyrodite-type crystal structure include Li 7-x PS 6-x Ha x (Ha is Cl or Br, x is preferably 0.2 to 1.8). The argyrodite-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks mainly appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°. Note that these peak positions may vary within a range of ±0.5°.

[0048] Here, since the sulfide solid electrolyte obtained by the above firing preferably contains lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, the aforementioned "Li 7-x P 1-y Si y S6, Li7+x P 1-y Si y S₆ (x is -0.6 to 0.6, y is 0.1 to 0.6)", when an atom other than a chlorine atom is used as the halogen atom in the compositional formula, the compositional formula "Li 7-x-2y PS 6-x-y Cl x (0.8≦x≦1.7, 0<y≦-0.25x+0.5)" may not be represented by the compositional formula. However, when the sulfide solid electrolyte obtained by the above firing has the same diffraction peaks as the diffraction peaks described as the diffraction peaks possessed by the "argyrodite-type crystal structure", it can be said that the sulfide solid electrolyte preferably has an argyrodite-type crystal structure formed of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms.

[0049] In the sulfide solid electrolyte obtained by the above firing, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms is preferably 1.0 to 1.8: 0.1 to 0.8: 1.0 to 2.0: 0.01 to 0.6, more preferably 1.1 to 1.7: 0.2 to 0.6: 1.2 to 1.8: 0.05 to 0.5, and still more preferably 1.2 to 1.6: 0.25 to 0.5: 1.3 to 1.7: 0.08 to 0.4. When bromine and iodine, or bromine and chlorine are used in combination as halogen atoms, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, bromine, and iodine (or chlorine) is preferably 1.0 to 1.8: 0.1 to 0.8: 1.0 to 2.0: 0.01 to 0.3: 0.01 to 0.3, more preferably 1.1 to 1.7: 0.2 to 0.6: 1.2 to 1.8: 0.02 to 0.25: 0.02 to 0.25, still more preferably 1.2 to 1.6: 0.25 to 0.5: 1.3 to 1.7: 0.03 to 0.2: 0.03 to 0.2, and even more preferably 1.35 to 1.45: 0.3 to 0.45: 1.4 to 1.7: 0.04 to 0.18: 0.04 to 0.18. The types and composition ratios (molar ratios) of the atoms constituting the sulfide solid electrolyte obtained by the above firing can be confirmed by, for example, an ICP emission spectrometer.

[0050] There are no particular restrictions on the shape of the sulfide solid electrolyte, but for example, particulate form can be given. The average particle size (D) of the particulate (crystalline) sulfide solid electrolyte. 50 Examples of these ranges include 0.01 μm to 500 μm and 0.1 to 200 μm.

[0051] (To obtain a sulfide solid electrolyte slurry) The manufacturing method of this embodiment includes wet grinding of the sulfide solid electrolyte and solvent obtained by the above-mentioned calcination using a pulverizer to obtain a sulfide solid electrolyte slurry. The above-mentioned pulverizer is literally a device used for pulverization, and while stirring and mixing may occur simultaneously with pulverization, as shown in Figure 1, the sulfide solid electrolyte obtained by calcination and the solvent may be mixed using a mixer before pulverization. The above-mentioned pulverizer is preferably a wet pulverizer capable of wet pulverization. Typical wet grinders include wet bead mills, wet ball mills, and wet vibratory mills. Wet bead mills, which use beads as the grinding medium, are preferred because they allow for free adjustment of the grinding conditions and are more suitable for materials with smaller particle sizes.

[0052] Furthermore, a flow-type pulverizer can be used that allows for circulating operation to recirculate the slurry to be pulverized as needed. Specifically, this includes a pulverizer that circulates the slurry between a pulverizer (pulverizer / mixer) that pulverizes the slurry and a temperature-maintaining tank (reaction vessel).

[0053] By selecting the size and material of the medium used (beads, balls), as well as the rotor rotation speed and time, mixing, stirring, grinding, or a combination of these processes can be performed, and the particle size of the resulting sulfide solid electrolyte can be adjusted to a desired size.

[0054] (solvent) As the solvent mentioned above, a wide range of solvents that have been conventionally used in the production of solid electrolytes can be adopted, such as hydrocarbon solvents including aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents. In addition to the hydrocarbon solvents mentioned above, other solvents that may be used include those containing atoms other than carbon atoms and hydrogen atoms, such as heteroatoms like nitrogen atoms, oxygen atoms, sulfur atoms, and halogen atoms.

[0055] (Drying using an air-flow dryer) The manufacturing method of this embodiment includes drying the above-mentioned sulfide solid electrolyte slurry using an air-jet dryer. By drying the sulfide solid electrolyte slurry obtained by the above wet grinding method using an air-jet dryer, aggregation of the sulfide solid electrolyte is reduced, and a sulfide solid electrolyte with a good particle size distribution can be efficiently obtained. This sulfide solid electrolyte does not contain coarse particles and has excellent coating properties when applied as a solution or slurry.

[0056] Drying using an airflow dryer can be performed by supplying a sulfide solid electrolyte slurry into an airflow of heated gas. Commercially available airflow dryers such as fluidized bed dryers and spray dryers, which have a mechanism for fluidizing media particles or other media with gas, can be used. As for the above-mentioned airflow dryer, from the viewpoint of further reducing the aggregation of sulfide solid electrolytes and efficiently obtaining sulfide solid electrolytes with a better particle size distribution, a spray dryer is preferred, and a spray dryer is more preferred, in which a fluid containing a sulfide solid electrolyte slurry is sprayed from a spray nozzle into a drying gas at a predetermined temperature to dry the fluid. By using a spray dryer as the above-mentioned airflow dryer, the obtained sulfide solid electrolyte does not contain coarse particles and has superior coating properties when applied as a solution or slurry.

[0057] One type of spray dryer is one in which a sulfide solid electrolyte slurry is sprayed from a spray nozzle along with a high-pressure gas, and then dried by contact with the heated gas. The above gas is preferably an inert gas. From the viewpoint of availability, nitrogen gas or argon gas is preferred as the inert gas.

[0058] The spray pressure in the spray dryer is preferably 0.01 to 0.8 MPa, more preferably 0.02 to 0.6 MPa, and even more preferably 0.03 to 0.5 MPa. When the spray pressure in the spray dryer is within the above range, the solvent in the sulfide solid electrolyte slurry can be sufficiently removed. Furthermore, aggregation of the sulfide solid electrolyte is further reduced, and a sulfide solid electrolyte with a better particle size distribution can be efficiently obtained.

[0059] From the viewpoint of better demonstrating the effects of the present invention, the droplet diameter of the spray liquid in the spray dryer is preferably 50 μm or less, more preferably 45 μm or less, and even more preferably 40 μm or less. As a lower limit, from the viewpoint of preventing change in the shape of the sulfide solid electrolyte due to shear force, it is preferably 1 μm or more, and more preferably 5 μm or more.

[0060] The operating conditions for the spray dryer can be appropriately determined according to the type of solvent contained in the sulfide solid electrolyte slurry, and since they vary depending on the boiling point of the solvent, etc., they cannot be specified in general terms. However, it is preferable that the temperature of the heated gas that comes into contact with the sulfide solid electrolyte slurry sprayed from the nozzle is 350°C or lower, as this allows the solvent to dry from the sprayed droplets at an appropriate speed and controls the particle size of the sulfide solid electrolyte. It is more preferable that it is 300°C or lower, even more preferable that it is 250°C or lower, and even more preferable that it is 230°C or lower. As a lower limit, from the viewpoint of shortening drying time and improving productivity, it is preferable that the temperature be 80°C or higher, and more preferably 100°C or higher.

[0061] Furthermore, the amount of sulfide solid electrolyte slurry supplied to the nozzle can vary depending on the scale of the spray dryer and cannot be set uniformly. It should be determined appropriately according to the scale, and is usually around 1 to 60 g / min. From the viewpoint of drying in a shorter time, it is preferably 3 to 50 g / min, more preferably 5 to 40 g / min, and even more preferably 10 to 30 g / min. The operating conditions for the spray dryer can be implemented, for example, by the method described in the examples.

[0062] From the viewpoint of efficiently collecting sulfide solid electrolytes having a desired particle size distribution, the spray dryer is preferably equipped with a bag filter. The fluid containing the gas supplied as a heat transfer medium and the sulfide solid electrolyte, which has passed through the spray dryer, can be fed into a bag filter, allowing only the gas to pass through, thereby recovering the sulfide solid electrolyte.

[0063] The filters used in bag filters are not particularly limited and can be made from materials such as polypropylene, nylon, acrylic, polyester, cotton, wool, heat-resistant nylon, polyamide / polyimide, PPS (polyphenylene sulfide), glass fiber, and PTFE (polytetrafluoroethylene). Functional filters, such as electrostatic filters, can also be used. Among these, filters made from heat-resistant nylon, polyamide / polyimide, PPS (polyphenylene sulfide), glass fiber, and PTFE (polytetrafluoroethylene) are preferred, filters made from heat-resistant nylon, PPS (polyphenylene sulfide), and PTFE (polytetrafluoroethylene) are more preferred, and filters made from PTFE (polytetrafluoroethylene) are particularly preferred. Furthermore, filters that have been processed to prevent fraying of the cut edges of the fabric at the end of the filter are preferred.

[0064] The bag filter may have a means for removing debris, for example, a pulsating back pressure method or a pulse jet method is preferred, with the pulse jet method being preferred. Furthermore, an induced draft fan may be installed in the line from the exhaust port of the bag filter to forcibly exhaust the gas being exhausted from the exhaust port.

[0065] The sulfide solid electrolyte obtained by the above drying process preferably has a volume-based particle size distribution with a peak in the range of particle size between 0.1 μm and less than 10.0 μm. This sulfide solid electrolyte does not contain coarse particles and exhibits excellent coating properties when applied as a solution or slurry. The crystal structure of the above sulfide solid electrolyte is the same as that described in the section on (sulfide solid electrolyte) above.

[0066] (Application) The sulfide solid electrolyte obtained by the manufacturing method of this embodiment does not contain coarse particles and can therefore be suitably used as an electrode. The above-mentioned sulfide solid electrolyte may be used in the positive electrode layer, the negative electrode layer, or the electrolyte layer. Each layer can be manufactured by known methods. When the above-mentioned sulfide solid electrolyte is used as an electrode mixture, it can be used as an electrode mixture containing the above-mentioned sulfide solid electrolyte and an electrode active material. As electrode active materials, positive electrode active materials and negative electrode active materials are selected depending on whether the electrode composite material is used as the positive electrode or the negative electrode. Conventional active materials can be used for the positive electrode and negative electrode active materials. In addition to the sulfide solid electrolyte and electrode active material, the material may also contain other components such as conductive materials and binders.

[0067] When the above-mentioned sulfide solid electrolyte is used as a battery, it can be used as a lithium-ion battery containing at least one of the above-mentioned sulfide solid electrolyte and the above-mentioned electrode composite material. Furthermore, the above-mentioned battery preferably uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer, and known current collectors can be used. For example, a layer coated with gold or the like, which reacts with the above-mentioned solid electrolyte, such as Au, Pt, Al, Ti, or Cu, can be used. [Examples]

[0068] The present invention will now be specifically described with reference to examples, but the present invention is not limited in any way by these examples.

[0069] (Measurement method) (1) Measurement of volume-based particle size distribution and average particle size In this embodiment, the volume-based particle size distribution was measured as follows. For the sulfide solid electrolytes obtained in Example 1 and Comparative Example 1, the volume-based particle size distribution was measured using a laser diffraction particle size distribution analyzer under the following measurement conditions, and the particle size (average particle size) corresponding to a cumulative frequency of 50% by volume from the smaller particle size side was calculated. The volume-based particle size distribution of the sulfide solid electrolyte is shown in Figure 2.

[0070] [Measurement conditions] Measurement device: Laser diffraction particle size distribution analyzer (LA-950V2 Model A2, manufactured by Horiba, Ltd.) Measurement standard: Volume Analysis conditions: Spherical shape and refractive index of 70% Particle size measurement range: 0.01 μm to 5000 μm

[0071] (2) Evaluation of coating properties The sulfide solid electrolyte and binder were weighed in a weight ratio of 98:2, and dehydrated butyl butyrate was gradually added and mixed with a spatula to create a slurry with a solid content of approximately 40-60%. This slurry was then processed in a THINKY ARE-310 rotary / revolving mixer at 2000 rpm for 5 minutes and then at 2200 rpm for 30 seconds to obtain a slurry for coating property evaluation. The slurry described above was dripped onto the deepest groove side of a BYK-Gardner grind gauge (0-100 μm), and a film was formed by pulling it towards the shallower groove side with a scraper. The groove depth at the point where streaks began to form was read, and the coating properties were evaluated from A to C according to the following criteria.

[0072] A: Streaks appear at a thickness of 20 μm or less. B: Streaks appear in areas greater than 20 μm and less than or equal to 50 μm. C: Streaks appear in particles larger than 50 μm and smaller than or equal to 80 μm.

[0073] (Manufacturing Example 1: Manufacturing of sulfide solid electrolyte (calcined product)) Lithium sulfide (manufactured by Idemitsu Kosan Co., Ltd.) was pulverized under a nitrogen atmosphere using a pin mill equipped with a quantitative feeder (model "100UPZ", manufactured by Hosokawa Micron Corporation) to an average particle size of 7.7 μm. Similarly, phosphorus pentasulfide (manufactured by Thermophos, average particle size: 125 μm), lithium chloride (manufactured by Honjo Chemical Co., Ltd., average particle size: 308 μm), and lithium bromide (manufactured by Honjo Chemical Co., Ltd., average particle size: 38 μm) were pulverized using a pin mill to obtain average particle sizes of 8.7 μm, 10 μm, and 5.0 μm, respectively.

[0074] In a glove box under a nitrogen atmosphere, lithium sulfide, diphosphorus pentasulfide, lithium chloride, and lithium bromide, which are the raw materials for the solid electrolyte, were weighed in a molar ratio of 47.5:12.5:25.0:15.0, totaling 110 g. These were placed in a glass container and roughly mixed by shaking the container. The roughly mixed raw material mixture was dispersed under a nitrogen atmosphere in a mixed solvent of 1140 mL of dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 7 mL of dehydrated isobutyronitrile (manufactured by Kishida Chemical Co., Ltd.) to obtain a slurry (containing approximately 10% by mass of the raw material). Next, the slurry was operated for 1 hour using a bead mill ("LMZ015 (model number)", manufactured by Ashizawa Finetech Co., Ltd.) to mix and grind the material, obtaining a slurry containing the ground raw materials.

[0075] The obtained slurry was transferred to a Schlenk bottle purged with nitrogen, and the solvent was removed by vacuum drying to obtain a dry product. The obtained dried material was fired in an electric furnace (model "F-1404-A", manufactured by Tokyo Glass Machinery Co., Ltd.) inside a glove box under a nitrogen atmosphere. Specifically, with the electric furnace temperature maintained at 430°C, the door of the electric furnace was opened, and a sagger (model "999-60S", made of Al2O3, manufactured by Tokyo Glass Machinery Co., Ltd.) containing 50g of the dried material was quickly placed inside. The door was then closed and the furnace was fired for 30 minutes. After that, the sagger was removed from the electric furnace, allowed to cool slowly, and then sieved using a 300μm mesh sieve to obtain a sulfide solid electrolyte (fired product).

[0076] (Example 1) The sulfide solid electrolyte (calcined product) obtained in Synthesis Example 1 was supplied to a bead mill ("LMZ015 (model number)", manufactured by Ashizawa Finetech Co., Ltd.) into which 5200 mL of dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., special grade) was added, and the mixture was mixed and pulverized under a nitrogen atmosphere to obtain a sulfide solid electrolyte slurry. The obtained sulfide solid electrolyte slurry was dried using a spray dryer ("CNL-3", manufactured by Okawara Chemical Machinery Co., Ltd.) as an airflow dryer, with a drying inlet temperature of 200°C and a spray pressure of 0.3 MPa to dry the solvent, and the average particle size (D 50 A 1.2 μm sulfide solid electrolyte was obtained. Nitrogen was used as the gas. The coating properties of the obtained sulfide solid electrolyte were evaluated as "A". Furthermore, as shown in Figure 2, it can be seen that the obtained sulfide solid electrolyte does not contain coarse particles with a particle size of 10 μm or larger. Therefore, it was confirmed that the method for producing sulfide solid electrolyte of this embodiment can produce a sulfide solid electrolyte that does not contain coarse particles and has excellent coating properties when applied as a solution or slurry.

[0077] (Comparative Example 1) The sulfide solid electrolyte slurry obtained in Example 1 was transferred to a Schlenk bottle, and the solvent was removed by vacuum drying. Then, it was dried for an additional hour in an oil bath at 100°C to obtain a sulfide solid electrolyte with an average particle size (D50) of 1.8 μm. The coating properties of the obtained sulfide solid electrolyte were evaluated as "C". [Industrial applicability]

[0078] The method for producing a sulfide solid electrolyte according to this embodiment can efficiently produce a sulfide solid electrolyte having a good particle size distribution. The obtained sulfide solid electrolyte is suitable for use in lithium-ion batteries, particularly in lithium-ion batteries used in automotive applications, as well as in information-related equipment and communication equipment such as personal computers, video cameras, and mobile phones, and especially in all-solid-state batteries.

Claims

1. The process of calcining the raw materials. The sulfide solid electrolyte obtained by the aforementioned calcination and the solvent are wet-ground using a pulverizer to obtain a sulfide solid electrolyte slurry, and A method for producing a sulfide solid electrolyte, comprising drying the sulfide solid electrolyte slurry using an air-jet dryer.

2. The method for producing a sulfide solid electrolyte according to claim 1, wherein the airflow dryer is a spray dryer.

3. The method for producing a sulfide solid electrolyte according to claim 2, wherein the spray pressure in the spray dryer is 0.01 to 0.8 MPa.

4. The method for producing a sulfide solid electrolyte according to claim 2 or 3, wherein the droplet diameter of the spray liquid in the spray dryer is 50 μm or less.

5. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 4, wherein the sulfide solid electrolyte obtained by the drying has a peak in the range of particle size 0.1 μm or more and less than 10.0 μm in volume-based particle size distribution.

6. A method for producing a sulfide solid electrolyte according to any one of claims 1 to 5, wherein the sulfide solid electrolyte obtained by drying is used as an electrode.

7. A method for producing a sulfide solid electrolyte according to any one of claims 1 to 6, wherein the raw material content includes lithium atoms, sulfur atoms, and phosphorus atoms.

Citation Information

Patent Citations

  • Solid electrolyte

    JP2020126760A

  • Method for producing reformed sulfide solid electrolyte powder

    WO2023276860A1